(untitled) (Journal of Engineering, 2007)
This paper introduces a new method in the multispectral image fusion based on ridgelet transform which represents edges better than wavelets. Since edges play a fundamental rule in image understanding, one good way to enhance spatial resolution is to enhance the edges. Ridgelet based image fusion method provides richer information in the spatial and spectral domains simultaneously. Also another method introduced based on new Hybrid transform which is improvement from the Ridgelet transform. Here we used our method to merge the panchromatic image of IKONOS sensor (1m resolution) with its multispectral image (4m resolution). The software used in this paper is (Matlab V 7.0.4 ).